Seroprevalence of cattle hydatidosis in some districts in the east Anatolian region of Turkey - Simsek, S; Köroglu, E; Dumanli, N; Aktas, I; Saki, CE; Altay, K; Ütük, AE (Tubitak Scientific & Technological Research Council Turkey, 2005)
Hydatidosis, caused by hydatid cysts, is a widespread and hazardous disease in humans and animals worldwide. The disease is very common in Turkey, causing serious economic losses. In this study, the seroprevalence of hydatidosis was determined by enzyme-linked immunosorbent assay (ELISA) and indirect fluorescence antibody technique (IFAT). A total of 597 serum samples were collected from cattle of various breeds and ages in 8 provinces in Eastern Turkey. Partially purified cyst fluid antigen from sheep hydatid cyst fluid was used as antigen in ELISA and whole protoscolex antigens were used in IFAT. The results showed that 63.3% and 54.9% of 597 cattle were positive with ELISA and IFAT, respectively. The highest seroprevalence was in Mu (85.3%) and the lowest was in Kars (46.6%) by ELISA. The seroprevalence was between 77.3% (Mu) and 35.1% (Erzurum) by IFAT.
Keywords: hydatidosis; cattle; ELISA; IFAT; seroprevalence